2012
DOI: 10.1002/asna.201211807
|View full text |Cite
|
Sign up to set email alerts
|

New results in RR Lyrae modeling: Convective cycles, additional modes and more

Abstract: Recent theoretical and observational findings breathed new life into the field of RR Lyrae stars. The ever more precise and complete measurements of the space asteroseismology missions revealed new details, such as the period doubling and the presence of the additional modes in the stars. Theoretical work also flourished: period doubling was explained and an additional mode has been detected in hydrodynamic models as well. Although the most intriguing mystery, the Blazhko-effect has remained unsolved, new find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The reason of its absence could be that it is in fact a non-radial mode close to the frequency of the second overtone. It can also be hypothesized that the excited mode exists in a parameter space that 1D models have avoided so far, similar to the discovery of period doubling and the low-amplitude first overtone in some RRab models (Molnár et al 2012). We note, however, that the mode was not detected during the extensive survey of those models.…”
Section: Additional Modes In Rrab Starssupporting
confidence: 70%
“…The reason of its absence could be that it is in fact a non-radial mode close to the frequency of the second overtone. It can also be hypothesized that the excited mode exists in a parameter space that 1D models have avoided so far, similar to the discovery of period doubling and the low-amplitude first overtone in some RRab models (Molnár et al 2012). We note, however, that the mode was not detected during the extensive survey of those models.…”
Section: Additional Modes In Rrab Starssupporting
confidence: 70%
“…Finally, non-linear hydrodynamic modelling of secondovertone Cepheids will be vitally important to determine whether mode resonances occur in these stars. Recent advancements in 1D pulsation codes revealed that both RR Lyrae and BL Herculis (short period Type II Cepheid) models may exhibit multimode pulsation, mode resonances, chaos, and small-amplitude modulation (Kolláth et al 2011;Molnár et al 2012;Plachy, Kolláth & Molnár 2013;Smolec & Moskalik 2012. If mode interactions can be identified in second-overtone Cepheid models, they will undoubtedly support the case of the mode resonance model, and will point towards a unified model for the Blazhko effect in Cepheid and RR Lyrae stars.…”
Section: Discussionmentioning
confidence: 94%
“…However, beside the period-doubled ones, chaotic hydrodynamic models were also found (Plachy, Molnár & Kolláth 2013). Further analysis showed that in these models the first overtone is also present and it is a crucial component in the occurrence of chaos (Molnár et al 2012a). Molnár et al (2012b) also argued that these three radial modes are present in the star RR Lyr.…”
Section: Introductionmentioning
confidence: 91%